Empowerment model by Village Owned Enterprises (BUMDes) realizing sustainable village tourism in Malang Regency - Rohman, Abd.; Rozikin, Mochammad; Adhitama, Muhammad Okto (Publisia: Jurnal Ilmu Administrasi Publik, 2023)
This research aims to describe the role and empowerment model of BUMDes in realizing sustainable village tourism, serving as a reference for policymakers in harnessing the potential towards effective governance. The data in this study is primarily collected through an in-depth analysis of purposively selected, relevant informants. Subsequently, the qualitative data obtained is analyzed using the Miles, Huberman, and Saldana model. The research findings reveal that empowerment, characterized by three indicators: conscientization, community organizing, and resource delivery, is not effectively carried out by BUMDes. Local communities respond to the presence of Cafe Sawah tourism independently, initiating businesses and trade within the Cafe Sawah area. BUMDes efforts to maintain the existence of Cafe Sawah tourism involve training and education for employees on rural tourism development, improving marketing management through enhanced social media promotion and conventional institution outreach, ensuring visitor comfort, delighting with natural scenery, providing local cuisine, and enhancing overall visitor experience. This study sheds light on the importance of BUMDes in fostering sustainable rural tourism while highlighting opportunities for improvement and development in their empowerment strategies